Teacher's Assistant Application - Janjikj, A; Madevska Bogdanova, Ana; Trajkovikj, Vladimir (IEEE, 2022)
With the start of the online teaching due to the COVID restrictions, the dynamics of the classes changed, and the Internet applications took a big swing in the education process. Before the COVID pandemic, teachers were forced to learn how to use web tools to deliver more productive teaching to pupils. But despite all the efforts of teachers and institutions to invest in quality online education, we are all witnesses that online instruction does not achieve the same effect as the teaching with a physical presence. We conducted several surveys in secondary and primary schools in the local area. The results lead to the conclusion that the attention of pupils and the quality of teaching is reduced compared to education with a physical presence. Teachers use paper notebooks, online teaching tools, online meeting scheduling tools, online assessment tools, and online homework tools from different sources. Surveys with teachers have also shown that they have difficulty dealing with inconsistent tools, paper records and most of the various software they use in their online teaching. This paper will examine the possibilities of the existing online applications for the above-mentioned teacher's needs. Following our survey results, we're creating an online tool that puts all the essential needs together, such as - keeping pupils' attention during classes, digitizing the teacher-led record section, quickly and easily assessing pupils, managing homeworks, working in groups on projects and automation of the previously listed processes. The main focus of this paper will be on our innovative application that will contribute to the work process of the teachers.
Keywords: online lecturing , online application , online education , primary and secondary education